Cystadenoma of the head of the pancreas - Campos Pierri, Néstor C.; Olivera, Daniel; Bergalli, Luis; Luksenburg, Jaime; Pradines, Jorge (Cirugía del Uruguay, 1978)
A 36-year-old woman had a cephalic cystoadenoma of the pancreas and was treated by cephalic duodenopancreatectomy with good postoperatory evolution. Histological study of any tumor is considered essential for the purpose of a definitive diagnosis.